EXPLORANDO O RACIOCÍNIO LÓGICO NO ENSINO DA MATEMÁTICA - Costa Iendez, Adriele; Lima Narciso, Pablo (LINKSCIENCEPLACE, 2026)
The present article aims to present aspects related to the exploration of the logical reasoning in the teaching, exposing reflections on the logical reasoning in the mathematics teaching, emphasizing the PCN and the LDB, the way in which the logical reasoning contributes in the learning of the student, when involved with questions of the your everyday life. It also analyzes teaching as a cumulative process of knowledge that must be started from elementary school, as a basis for the student upon reaching high school. In addition, the difficulties that the students present in the understanding of exercises and rules in the study of mathematics are highlighted. It is worth noting the use of games as a pedagogical tool, which should be used by the teacher in order to arouse the student’s interest in a playful way, being used as an aid in the fixing of contents. Thus, presenting the need to study mathematics as a way to train students able to solve and solve problem situations.